Ungkapan Satire Al-Qur’an Dalam Mujadalah (Seni Kesantunan Komunikasi, Artikulasi, dan Agregasi Politik Menghadapi Penguasa) - Muhammad Haris Hakam (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2022)
The world of da'wah is very close to delivering messages in the form of narratives. Da'wah does not always run smoothly, even during the times of the Prophets and Apostles, da'wah is a difficult and full of suffering. When da'wah collided with power, the apostles were even ordered to continue to convey their message of da'wah to the rulers. The story is a miracle of the Koran. One of the stories in the Koran that describes the human process in achieving the truth can be seen in the story of Abraham in seeking God. The procession of seeking God was carried out by Ibrahim by observing material objects with the naked eye, thinking about them and finding God's truth through the potential of his heart. Ibrahim started by empowering the potential of the body (physical), then the potential of the mind (akliah, ratio) and finally the potential of the heart (qalbu). All of these are practical steps for humans in finding the truth. The communication of Prophet Musa's da'wah to Pharaoh in the Qur'an shows that Moses' prophetic mission was. is to liberate the people from the grip of the rulers. Collaborative communication of da'wah model of the Prophet Ibrahim (as) and Prophet Musa (as) in the face of unjust and arbitrary rulers is summed up in an idiom: